Transmembrane Phosphatase with TEnsin Homologue (TPTE) Expression in Epithelial Ovarian Cancer - CA Adepiti; K Odunsi (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2022)
Background: TPTE is a 'Cancer Testis' antigen that could be a candidate for targeted immunotherapy of epithelial ovarian cancer. Objective: To determine the prevalence of expression and the impact of TPTE on clinical and survival outcomes in epithelial ovarian cancer. Methods: Relevant medical information of 173 ovarian cancer patients (including Fallopian and primary peritoneal) managed at a Cancer Centre were retrieved. Reverse-transcriptase polymerase chain reaction (RT-PCR) was used to detect the expression of TPTE in the tumours. TPTE expression was correlated with the clinicopathologic and survival outcomes of the patients. Results: TPTE was expressed by 45.1% (78/173) of the tested tumours. There was no significant difference in age between TPTE-positive and negative women (p = 0.93). TPTE expression was not significantly associated with the stage of the disease (p = 1.00), grade of disease (p = 0.71) and histology of the tumour (p = 0.17). There was no significant association between TPTE expression and the ease of optimum debulking (44.5% vs 44.3%, p = 0.54). TPTE expression was also not associated with a better response to therapy (p = 0.05). However, it was associated with slightly longer but not statistically significant progression-free survival (27.5 vs 20.6-months, p = 0.14) and overall survival (49.2 vs 28.0 months, p = 0.11). Conclusion: This study shows that TPTE is expressed at a moderate frequency in epithelial ovarian cancers, and its expression is associated with marginally better survival outcomes.